I am legend - Matheson, Richard, 1926-2013 (ORB, 1995)
"Robert Neville is the last living man on Earth ... but he is not alone. Every other man, woman, and child on Earth has become a vampire, and they are all hungry for Neville's blood"--Publisher's description, I am legend.